Strategi Pendidikan dan Pembelajaran PAI Berbasis Penemuan (Discovery-Based Learning) di MI Hidayatul Mubtadiin Jrakahpayung Kecamatan Tulis Batang - Winarno, Winarno (Lembaga Yasin AlSys, 2024)
This article aims to find out the learning model of PAI based on discovery learning, describe the planning strategy for implementing the learning model of PAI based on discovery learning, describe the types of learning based on discovery learning, know the advantages and virtues of the learning model based on discovery learning. This type of research is qualitative. For data analysis, researchers do by means of data reduction. With the discovery learning-based PAI education and learning strategy, it is expected that the learning process and PAI learning can be carried out properly so as to improve teaching and learning outcomes. This can be effective because the discovery learning model places students in a conditioned environment in the form of an exploratory learning design, where students play an active role in learning in class by exploring the subject matter. In accordance with the characteristics of fiqh subjects that foster the ability to explore the values of Islamic teachings in the subject matter intensely which can then be applied and implemented relevantly in everyday life.